First Detection of Tetrodotoxin in the Bivalve Paphies australis by Liquid Chromatography Coupled to Triple Quadrupole Mass Spectrometry With and Without Precolumn Reaction. (27th November 2019) - McNabb, Paul S; Taylor, David I; Ogilvie, Shaun C; Wilkinson, Larn; Anderson, Alice; Hamon, David; Wood, Susanna A; Peake, Barrie M
Abstract: Two methods for the determination of tetrodotoxin(TTX) in marine biota have been developed and validated using ultra-performance LC coupled to triple quadrupole MS. The direct analysis of TTX is completed in one method, while the other method detects the dehydration product of TTX after reaction with base. The methods were validated in a single-laboratory trial and used to test Paphies australis (pipi) samples collected from Whangapoua, New Zealand during April 2011. Pa. australis is a commonly eaten species of bivalve that was found to contain TTX at levels up to 0.80 mg/kg in this study. The methods exhibited recoveries ranging from 94 to 120%, and the within laboratory reproducibility ranged from 6 to 27% for Pleurobranchaea maculata (grey-side gilled sea slug) andbivalve matrixes. Use of the method using a dehydration step showed no evidence of TTX analogs in any ofthe samples.